Maintien de la paix et réforme des Nations Unies - Legault, Albert (Études internationales, 1996)
Even though substantial administrative and financial changes have been introduced in the United Nations since the early 1980s, the end of the Cold War has brought about a turning point in its process of reform. The impressive growth of UN peacekeeping operations has tipped the balance in favor of major transformations in this field. Indeed, since the publication of the Secretary General’s (Agenda for Peace) many changes have been undertaken and improvements achieved. However much still needs to be done. This paper addresses three particular issues: institutional reforms, organizational reforms and reforms through adjustments. While little will be said on the first two issues, since they are relatively well known and treated elsewhere, this paper will focus on UN'S peacekeeping operations and their actual evolution as a way of assessing the continuing process of reform in the United Nations.